Detection of intracavitary lesions in 436 infertile women by office hysteroscopy and comparison with histopathology results (Annals of Medical Research, 2021)
Aim: To examine the importance of office hysteroscopy in detecting and treating endometrial pathologies of infertile patient groups.Materials and Methods: For this retrospective observational study, first, electronic hospital records were examined in order to identify patients who underwent office hysterescopy at our clinic, between 2003 and 2020, for infertility. The office hysteroscopy findings of 436 patients were included in the study, and examined and compared with the histopathological results.Results: The age distribution of the patients included in the study was homogeneous in terms of group variances. Thehysteroscopy findings of the patients were as follows: normal cavityin 137 patients(31.4%), endometrial polyps in 199 patients(45.6%), synechia in 14 patients(3.2%), subseptum or arcuate uterus in 32 patients (7.3%), t-shaped uterus in 28 patients (6.4%), cervical polyps in 6 patients (1.4%), Asherman’s syndrome in 6 patients (1.4%), and submucous myoma in 14 patients (3.2%). The most frequently detected lesion with office hysteroscopy was polyps,at a rate of 47% with 205 patients. In the pathology results, of the 137 patients who were diagnosed with normal endometrium via office hysteroscopy and underwent biopsy, 119were reported as normal (89.6%), while 6 were diagnosed with polyps (4.4%). The sensitivity and specificity of office hysteroscopy in detecting endometrial polyps were 94% and 56%, respectively.Conclusion: Office hysteroscopy may be one of the first alternative methods that can be used for safe and practical outpatient diagnosis and treatment in infertile patient groups.
Keywords: Histopathology; infertility; office hysteroscopy